2011
DOI: 10.1098/rspb.2011.0433
|View full text |Cite|
|
Sign up to set email alerts
|

Reservoirs of richness: least disturbed tropical forests are centres of undescribed species diversity

Abstract: In the last few decades, there has been a remarkable discovery of new species of plants, invertebrates and vertebrates, in what have been called the new age of discovery. However, owing to anthropogenic impacts such as habitat conversion, many of the still unknown species may go extinct before being scientifically documented (i.e. 'crypto-extinctions'). Here, by applying a mathematical model of species descriptions which accounts for taxonomic effort, we show that even after 250 years of taxonomic classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 38 publications
(58 reference statements)
2
49
0
Order By: Relevance
“…Despite being flagged among the ''biodiversity hotspots'' (Myers et al 2000), this biome is still being degraded at a fast/steady pace (Ribeiro et al 2009). In the last decades many studies have revealed a large underestimation of amphibian species occurring in the Atlantic Forest (Giam et al 2012) and previously unrecognized lineages sometimes >10 millions of years old (e.g. Fouquet et al 2012 …”
Section: Introductionmentioning
confidence: 99%
“…Despite being flagged among the ''biodiversity hotspots'' (Myers et al 2000), this biome is still being degraded at a fast/steady pace (Ribeiro et al 2009). In the last decades many studies have revealed a large underestimation of amphibian species occurring in the Atlantic Forest (Giam et al 2012) and previously unrecognized lineages sometimes >10 millions of years old (e.g. Fouquet et al 2012 …”
Section: Introductionmentioning
confidence: 99%
“…That is, the undescribed species are likely to have small distributions, are geographically concentrated and possibly already threatened (Pimm et al 2014;Giam et al 2012). For fungi, the situation is even more serious, as we do not know how many species are yet to be discovered.…”
Section: Discussionmentioning
confidence: 93%
“…The greatest numbers of undescribed species are likely to be in tropical moist forests of the Neotropics, the Afrotropics and Indomalaya with minimal anthropogenic disturbance, and consequently, are less studied and scientifically explored in comparison with other biomes (Giam et al 2012). Nevertheless, few areas are protected in many of these biomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonetheless, the structural complexity of tropical forests combined with the diversity of niches and warm, moist climates make it a near certainty that large numbers, if not the majority, of undescribed fungal species reside in the tropics (Hawksworth 1993) as has been determined for some vertebrate groups (Giam et al 2012).…”
mentioning
confidence: 99%